BENTUK PERUSAHAAN JASA ANGKUTAN SEWA KHUSUS MENURUT PERATURAN MENTERI PERHUBUNGAN NOMOR 118 TAHUN 2018 - Siti Mariyam (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2019)
The industrial revolution 4.0 has influenced businesses in the field of trade in goods and services. In the trade of services, a new type of online rental service / taxi has emerged. Special leased transportation is a door-to-door transportation service with drivers who have operational areas in urban areas, from airports to airports, ports or other transportation nodes and reservations using information technology-based applications, with the tariff rates listed in the application. The implementation of this special rental transportation is based on the Regulation of the Minister of Transportation Number 118 of 2018 concerning the Implementation of Special Rental Transportation. To provide legal certainty on aspects of safety, security, comfort, equality, afford ability, and regularity for the community over the implementation of special rental transportation, and to support development to realize public welfare as mandated by the 1945 Constitution of the Republic of Indonesia.